Acid-resistant polyurethane adhesive, and preparation method and use thereof

CN122958975APending Publication Date: 2026-10-23NANPAO RESINS (FOSHAN) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611236348.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-08-03
Filing Date
2026-08-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0006]综上所述,现有耐酸型聚氨酯粘胶剂技术难以同时满足耐酸、低温柔韧的核心性能要求

Benefits of technology

本发明通过分子主链、交联网络、填料分散及界面结合的多层次协同,实现了耐酸与耐低温性能的统一。本发明粘胶剂在常温的20%硫酸中浸泡30天后,拉伸强度保持率达90%及以上,断裂伸长率保持率可达88%及以上;在常温的20%硫酸中浸泡30天后并转移至-30℃条件下冷冻处理7天后,拉伸强度保持率达86%及以上,断裂伸长率保持率可达83%及以上,实现了耐强酸、耐低温的性能突破。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses an acid-resistant polyurethane adhesive as well as a preparation method and application thereof, in particular to a low-temperature-resistant and acid-resistant polyurethane adhesive, and belongs to the technical field of acid-resistant and low-temperature-resistant polyurethane adhesives. The adhesive is composed of A and B components, wherein the A component is a hydroxyl component, and the B component is an isocyanate component. The acid resistance, hydrolysis resistance and low-temperature flexibility of the polyurethane adhesive are remarkably improved through the compounding of polycarbonate diols and hydroxyl-terminated polybutadiene in a specific ratio as soft segments, the synergistic effect of rigid cage structure chain extenders and furan ring structure chain extenders, the adhesive can be used stably for a long time in a low-temperature and acid corrosion environment, and is suitable for bonding and sealing applications in the fields of low-temperature chemical pipelines, low-temperature pickling equipment and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of acid- and low-temperature resistant polyurethane adhesives, and particularly relates to a low-temperature resistant and acid-resistant polyurethane adhesive. Background Technology

[0002] Polyurethane adhesives are widely used in construction, automotive, electronics, and aerospace industries due to their excellent bonding properties, adjustable mechanical properties, and good low-temperature resistance. However, the industry has made many attempts to improve the acid resistance of polyurethane adhesives, but traditional polyurethane adhesives face severe performance challenges in highly acidic corrosive environments.

[0003] (a) Failure of ordinary polyurethane adhesives in acidic environments Ordinary polyurethane adhesives are prone to hydrolysis of urethane bonds in acidic media, leading to softening of the adhesive layer, decreased bonding strength, and even debonding failure, making them unsuitable for long-term use in strong acid environments. For example, although patent CN103045153A achieves a certain acid resistance through a polyether polyol + acid-resistant filler system, its soft segment uses polyether polyol, which still carries the risk of chain degradation under 20% sulfuric acid immersion conditions.

[0004] (ii) Limitations of improving media resistance by increasing crosslinking density To improve the acid and media resistance of polyurethane adhesives, a common approach in the industry is to increase the crosslinking density of the system. However, excessively high crosslinking density often leads to increased brittleness and reduced elongation at break, especially noticeable in low-temperature environments (such as -20°C), manifesting as adhesive cracking and bonding failure. Patent CN113831885A adopts a technical route of increasing crosslinking density by introducing thermoplastic phenolic resin to improve acid and alkali resistance, but this solution has limited flexibility in low-temperature environments and cannot meet the requirements of acidic low-temperature bonding scenarios.

[0005] (III) Application of polycarbonate diol (PCDL) in hydrolysis-resistant polyurethane Polycarbonate-based polyurethanes exhibit superior hydrolysis and chemical resistance compared to polyester-based polyurethanes due to the better chemical stability of carbonate bonds compared to ester bonds. Patent CN113461905A discloses the preparation of polyurethane elastomer sealing materials using PCDL as the soft segment, confirming the advantages of PCDL-based polyurethanes in hydrolysis and chemical resistance. However, it does not present a PCDL+HTPB soft segment composite, nor does it include a system design for extreme operating conditions involving strong acids and low temperatures.

[0006] In summary, existing acid-resistant polyurethane adhesive technologies struggle to simultaneously meet the core performance requirements of acid resistance and low-temperature flexibility. In applications such as interface bonding and corrosion sealing of chemical pipelines, lining bonding and joint sealing of pickling equipment, joint sealing and corrosion repair of chemical storage tanks, and sealing and bonding of acidic raw material storage and transportation containers, these deficiencies can lead to problems like adhesive layer cracking, bonding failure, and corrosion penetration at temperatures as low as -20°C. These issues severely impact the safe and stable operation of equipment, increasing maintenance costs and safety hazards.

[0007] Therefore, developing a polyurethane adhesive that combines strong acid resistance and low-temperature flexibility, namely, a tensile strength ≥90% after immersion in 20% sulfuric acid for 30 days and an elongation at break ≥83% after immersion in 20% sulfuric acid for 30 days and freezing at -30℃ for 7 days, has become an urgent technical challenge to be solved in the field. Summary of the Invention

[0008] To address the problems existing in the background art, the first aspect of the present invention provides a polyurethane adhesive, employing the following technical solution: The polyurethane adhesive is composed of component A and component B mixed in a certain proportion.

[0009] The weight range and preferred weight of each component in component A are shown in Table 1.

[0010] Table 1: Weight range and preferred weight of each component in Component A

[0011] The acid-resistant filler is one or more of silica fume, mica powder, and barium sulfate. Preferably, the ratio of each component of the acid-resistant filler is silica fume:mica powder:barium sulfate = 2:1:1.

[0012] The weight range and preferred weight of each component in component B are shown in Table 2.

[0013] Table 2: Weight range and preferred weight of each component in Component B

[0014] The NCO / OH molar ratio of this invention is 1:1.05 to 1.18; preferably, the NCO / OH molar ratio is 1:1.12.

[0015] The present invention includes the following steps 1. Preparation of component A: ①. Raw material pretreatment: The raw materials are dehydrated to remove as much moisture as possible. Specifically, the flexible segments, chain extenders, and DOTP are dehydrated under vacuum at 80-105℃ for 1-2 hours; the functional fillers are dried in an oven at 105-110℃ for 4-5 hours to remove adsorbed water.

[0016] ②. Raw material mixing and dispersion: The component raw materials are mixed and dispersed at high speed. Specifically, the flexible segments, chain extenders and DOTP are added to the reactor and dispersed at high speed at 80-100℃ until a uniform and transparent mixture is formed.

[0017] ③. Addition of additives: After the mixture prepared in ② has cooled to 50-60℃, add coupling agent, functional filler, PCDI, and bismuth acetylacetone. Continue stirring and dispersing for 30-60 minutes to ensure that all components of the system are fully mixed and homogeneous. After degassing, discharge the material, seal and package it for storage, which is component A.

[0018] 2. Preparation of Component B: The liquefied MDI and HDI trimer are added to a dry reaction vessel in proportion, stirred and mixed evenly under nitrogen protection, degassed, discharged, sealed and packaged for storage, which is Component B.

[0019] 3. Two-component mixing: Mix component A and component B in the specified proportions until homogeneous, then apply as a sizing agent. Preferably, components A and B are mixed in an environment with a protective gas (such as nitrogen).

[0020] Compared with the prior art, the present invention has the following beneficial technical effects: This invention achieves a unified performance in acid resistance and low-temperature resistance through multi-level synergy of the molecular backbone, cross-linked network, filler dispersion, and interfacial bonding. The adhesive of this invention, after being immersed in 20% sulfuric acid at room temperature for 30 days, retains 90% or more of its tensile strength and 88% or more of its elongation at break. After being immersed in 20% sulfuric acid at room temperature for 30 days and then frozen at -30°C for 7 days, it retains 86% or more of its tensile strength and 83% or more of its elongation at break, achieving a breakthrough in resistance to strong acids and low temperatures.

[0021] Applications of this invention: This invention can be used for bonding and sealing in low-temperature acidic corrosive environments, specifically including bonding and anti-corrosion sealing of interfaces of chemical pipelines, bonding and sealing of linings of pickling equipment, sealing and anti-corrosion repair of joints of chemical storage tanks, and sealing and bonding of acidic raw material storage and transportation containers; this invention can withstand low-temperature conditions down to -20°C. Detailed Implementation

[0022] To enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below through embodiments and comparative examples. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0023] In the following examples and comparative examples, all raw materials used were commercially available conventional raw materials, including: PCDL with a number average molecular weight of 1000 and OH molar number of 187 mgKOH / g; HTPB with a number average molecular weight of 1000 and OH molar number of 185 mgKOH / g; and PDMS with a number average molecular weight of 1000 and OH molar number of 194 mgKOH / g.

[0024] Example 1 This embodiment provides an acid-resistant polyurethane adhesive, composed of component A and component B, with an NCO / OH molar ratio of 1:1.12.

[0025] In this embodiment, the components of component A and their corresponding weight parts are as follows: PCDL 48 parts, HTPB 12 parts, PDMS 4 parts, FDM 5.2 parts, 1,3-adamantimil 7 parts, silane coupling agent KH-550 1.7 parts, acid-resistant filler 14 parts, PCDI 3 parts, FS 2 parts, bismuth acetylacetone 0.1 parts, and DOTP 3 parts.

[0026] In this embodiment, the components of group B and their corresponding weight parts are as follows: 80 parts of liquefied MDI and 20 parts of HDI trimer.

[0027] In this embodiment, component A is prepared as follows: ① Raw material pretreatment: Dehydrate the flexible segments, chain extender and DOTP under vacuum at 90℃ for 1.5 hours; dry the functional filler in an oven at 108℃ for 4.5 hours to remove adsorbed water.

[0028] ② Raw material mixing and dispersion: Add flexible segments, chain extenders and DOTP into the reactor and disperse them at high speed at 90°C until a uniform and transparent mixture is formed.

[0029] ③ Addition of additives: After the polyol mixture cools down to 55℃, add coupling agent, functional filler, PCDI, and bismuth acetylacetone. Continue stirring and dispersing for 40 minutes to ensure that all components of the system are fully mixed and homogeneous. After degassing, discharge the material, seal and package it for storage, which is component A.

[0030] In this embodiment, component B is prepared as follows: The liquefied MDI and HDI trimer are added to a dry reactor, stirred and mixed evenly under nitrogen protection, degassed, discharged, sealed and packaged for storage, which is component B.

[0031] When using, mix and stir component A and component B thoroughly under nitrogen protection before applying the adhesive.

[0032] Examples 2-7 Examples 2-7 each provide an acid-resistant polyurethane adhesive, composed of component A and component B.

[0033] The differences in the weight proportions of each component in components A and B of Examples 2-7 are shown in Tables 3 and 4.

[0034] Table 3: Formulations of Component A in Examples 2-7

[0035] Table 4: Formulations of Component B in Examples 2-7

[0036] The preparation methods of Examples 2-7 are basically the same as those of Example 1, except that: Example 2: Vacuum dehydration temperature 80℃, dehydration time 1.2 hours; oven drying temperature 105℃, drying time 4.2 hours; raw material mixing and dispersion temperature 80℃; NCO / OH molar ratio 1:1.07.

[0037] Example 3: Vacuum dehydration temperature 80℃, dehydration time 1.2 hours; oven drying temperature 105℃, drying time 4.2 hours; raw material mixing and dispersion temperature 80℃; NCO / OH molar ratio 1:1.1.

[0038] Example 4: Vacuum dehydration temperature 95℃, dehydration time 1.6 hours; oven drying temperature 107℃, drying time 4.6 hours; raw material mixing and dispersion temperature 92℃; NCO / OH molar ratio 1:1.05.

[0039] Example 5: Vacuum dehydration temperature 95℃, dehydration time 1.6 hours; oven drying temperature 107℃, drying time 4.6 hours; raw material mixing and dispersion temperature 92℃; NCO / OH molar ratio 1:1.18.

[0040] Example 6: Vacuum dehydration temperature 105℃, dehydration time 2 hours; oven drying temperature 110℃, drying time 5 hours; raw material mixing and dispersion temperature 100℃; NCO / OH molar ratio 1:1.14.

[0041] Example 7: Vacuum dehydration temperature 105℃, dehydration time 2 hours; oven drying temperature 110℃, drying time 5 hours; raw material mixing and dispersion temperature 100℃; NCO / OH molar ratio 1:1.06.

[0042] Comparative Examples 1-9 The formulations of Comparative Examples 1-9 are basically the same as those of Example 1, except that: Comparative Example 1 without PCDL; Comparative Example 2: No HTPB added; Comparative Example 3: No PDMS added; Comparative Example 4 without FDM; Comparative Example 5 did not contain 1,3-adamantimil; Comparative Example 6 without FS; Comparative Example 7: No acid-resistant filler added; Comparative Example 8: No liquefied MDI added; Comparative Example 9: No HDI trimer added.

[0043] The preparation methods of Comparative Examples 1 to 9 are basically the same as those of Example 1, except that the missing components need to be omitted in the corresponding steps.

[0044] Comparative Examples 10-13 The preparation methods and weight ratios of components A and B in Comparative Examples 10-13 were the same as in Example 1. The differences in the amount of each component added from Comparative Examples 1 are shown in Tables 5 and 6.

[0045] Table 5: Formulations of Component A in Comparative Examples 10–13

[0046] Table 6: Formulations of Component B in Comparative Examples 10–13

[0047] Comparative Examples 14–17 The formulations of Comparative Examples 14-17 are basically the same as those of Example 1, except that some components have changed, specifically: Comparative Example 14 replaced PCDL with an equal part by weight of polytetrahydrofuran diol; Comparative Example 15 replaced HTPB with an equal part by weight of polycaprolactone diol; Comparative Example 16 replaced liquefied MDI with an equal part by weight of toluene diisocyanate (TDI-80); Comparative Example 17 replaced the HDI trimer with an equal part by weight of HDI biuret.

[0048] The weight ratio of components A and B in Comparative Examples 14-17 was the same as that in Example 1.

[0049] The preparation methods of components A and B in Comparative Examples 14-17 are basically the same as those in Example 1, except that the replaced component is replaced by the added component in the corresponding step.

[0050] Comparative Example 18 This comparative example describes the preparation of an acid-resistant two-component polyurethane adhesive according to the formulation and method of Example 1 in Chinese Patent CN103045153A. The adhesive consists of a mixture of component A and component B in a weight ratio of 6:1. Component A is primarily composed of polypropylene oxide polyol as the main resin, supplemented with 1,4-butanediol chain extender, silica fume acid-resistant filler, dibutyl phthalate plasticizer, carbodiimide hydrolytic stabilizer, oxazolidine water absorbent, silane coupling agent, fumed silica thixotropic agent, and organotin catalyst. Component B is a mixture of polyisocyanate resin and plasticizer.

[0051] Comparative Example 19 This comparative example prepares a high-adhesion, acid- and alkali-resistant reactive polyurethane hot melt adhesive according to the formulation and method of Example 3 in Chinese Patent CN113831885A. This hot melt adhesive uses 3-methyl-1,5-pentanediol sebacate (MPD / SA) as the polyester polyol, adds polyphenol oxycarbonate (PKHB), uses terephthalic diisocyanate (PPDI) as the isocyanate component, and is supplemented with mercaptopropyltrimethoxysilane coupling agent and bismorpholine diethyl ether catalyst. It is prepared as an NCO-terminated reactive hot melt adhesive through a prepolymerization reaction, and forms a cross-linked structure through moisture curing during use.

[0052] Comparative Example 20 This comparative example prepares a polycarbonate-type polyurethane elastomer sealing material according to the formulation and method of Example 2 in Chinese Patent CN113461905A. The elastomer uses polycarbonate diol (PCDL) as the soft segment, toluene diisocyanate (TDI) as the hard segment, and trimethylolpropane (TMP) as the crosslinking agent. It is formed by prepolymer casting and cured at 80°C for 24 hours to obtain a fully crosslinked polycarbonate-type polyurethane elastomer.

[0053] Performance testing methods The specific test items and methods are as follows: 1. Sample preparation: Referring to CN113461905A and the international standard ISO-527-2 / 5B, the sample was prepared into a dumbbell shape with a narrow section diameter of 2±0.2mm. 2. Initial value test: The initial tensile strength and elongation at break were tested using a universal testing machine (Shimadzu AG-Xplus).

[0054] 3. Acid resistance test: Refer to CN109401713A, the acid resistance of polyurethane is tested by immersion in sulfuric acid. The difference is that the concentration of sulfuric acid is increased from 10% to 20%.

[0055] ① Acid treatment retention rate test: The sample prepared in step 1 was immersed in a 20% sulfuric acid solution at room temperature for 30 days. After immersion, the sample was removed and its tensile strength and elongation at break were tested. The "acid treatment tensile strength retention rate" and "acid treatment elongation at break retention rate" were calculated. Acid treatment tensile strength retention rate = (Tensile strength after immersion / Initial tensile strength) × 100%; Acid treatment elongation at break retention rate = (Elongation at break after immersion / Initial elongation at break) × 100%.

[0056] ② Low-temperature acid treatment retention rate test: The cured sample was immersed in a 20% sulfuric acid solution at room temperature for 30 days, then transferred to -30℃ for freezing treatment for 7 days. After removal, the tensile strength and elongation at break were tested at -30℃, and the "low-temperature + acid treatment tensile strength retention rate" and "low-temperature + acid treatment elongation at break retention rate" were calculated. Low-temperature + acid treatment tensile strength retention rate = tensile strength after sulfuric acid immersion and freezing treatment / initial tensile strength × 100%; Low-temperature + acid treatment elongation at break retention rate = elongation at break after sulfuric acid immersion and freezing treatment / initial elongation at break × 100%.

[0057] Performance test results Table 7 Performance test results of polyurethane adhesives

[0058] As shown in Table 7, compared with Comparative Examples 1-20, Examples 1-7 use polycarbonate diol and hydroxyl-terminated polybutadiene as soft segments, and with the synergistic effect of multiple components such as chain extenders, furan structures, siloxane modification, acid-resistant fillers and polycarbodiimide, the prepared two-component polyurethane adhesive has excellent acid resistance and low-temperature resistance.

[0059] Specifically: (1) Soft segment compound balances acid resistance and low temperature toughness Comparative Example 1, which lacks PCDL and uses HTPB as the main soft segment, shows that the tensile strength retention rates of the polyurethane obtained after acid treatment and low-temperature + acid treatment are only 68% and 55%, respectively. Comparative Example 2, which lacks HTPB and uses PCDL as the single soft segment, shows that the elongation at break after low-temperature + acid treatment of the resulting polyurethane is only 55%, and the low-temperature flexibility is significantly deteriorated. Comparative Examples 10 and 11 combined PCDL and HTPB, but the ratio was unbalanced: In Comparative Example 10, PCDL was excessive (65 parts) and HTPB was insufficient (6 parts), resulting in low-temperature toughness deterioration, and the tensile strength retention rate after low-temperature + acid treatment was only 78%; In Comparative Example 11, HTPB was excessive (18 parts), resulting in an initial tensile strength decrease to 6.5 MPa.

[0060] In Comparative Example 14, after replacing PCDL with polytetrahydrofuran diol, the retention rate of tensile strength after acid treatment decreased to 72%, which is much lower than the 89% and above of the examples. This demonstrates that in the specific polyol-chain extender-isocyanate synergistic system of the present invention, PCDL can better form a dense barrier layer with low free volume with other functional components compared to PTMG, thereby improving the overall acid corrosion resistance. In Comparative Example 15, after replacing HTPB with polycaprolactone diol, the tensile strength retention rate after low-temperature + acid treatment decreased to 70%, and the low-temperature toughness deteriorated significantly, demonstrating the key role of the butadiene structure of HTPB in low-temperature toughness.

[0061] Examples 1-7 show that PCDL and HTPB were compounded in a suitable ratio, i.e., 40-65 parts PCDL and 8-16 parts HTPB. The retention rate of tensile strength after acid treatment and the retention rate of tensile strength after low temperature + acid treatment reached 90% and 85% and 85% and 85% and 85% respectively, achieving a balance between acid resistance and low temperature flexibility.

[0062] (2) Synergistic effect of multiple hydrophobic and densification to resist acid corrosion This mechanism resists acid corrosion through the synergistic effect of multiple hydrophobic and densification processes, specifically manifested in the following three aspects: ① The hydrophobic layer on the PDMS surface and the bulk hydrophobicity of the rigid chain extender together reduce acid penetration.

[0063] In Comparative Example 3, after PDMS was missing, the retention rate of tensile strength after low temperature + acid treatment decreased from 85% to 93% in the examples to 80%, and the acid resistance decreased significantly. Comparative Example 5, lacking the rigid cage-like structure of 1,3-adamantanediethanol, exhibited a tensile strength retention rate of only 75% after acid treatment, far lower than the 89%–97% of the Examples, indicating a significant deterioration in the bulk phase's resistance to acid media.

[0064] ② The rigid furan ring structure of FDM improves the regularity and packing density of hard segments, enhances the cohesive energy of hard segments, and the rigid cage-like structure segments work together to form a stronger barrier structure.

[0065] In Comparative Example 4, after the absence of FDM, the retention rate of tensile strength after acid treatment decreased to 82%, and the retention rate of tensile strength after low temperature + acid treatment decreased to 78%. The decrease in the density of the physical cross-linked network made the acid solution more easily penetrate.

[0066] ③ Acid-resistant filler combined with KH-550 reduces interfacial gaps and delays acid seepage channels along the interface.

[0067] In Comparative Example 7, the retention rate of tensile strength after acid treatment was only 80% after the absence of acid-resistant filler, indicating a reduction in physical isolation effect. Comparative Example 6 showed a slight decrease in acid resistance after the absence of FS.

[0068] The above-mentioned multiple synergistic effects helped the acid-treated tensile strength retention rate of the embodiment to remain stable at 90% to 97%, and the low temperature + acid treatment elongation at break retention rate to remain at 83% to 89%.

[0069] (3) Isocyanate compounding to strengthen cross-linking network This mechanism constructs a three-dimensional network through isocyanate complexes and combines it with hydrolysis stabilizers to ensure long-term acid resistance, specifically manifested in the following three aspects: ① The liquefied MDI and HDI trimer are combined to form a three-dimensional network that combines rigidity and flexibility.

[0070] Comparative Example 8, which uses HDI trimer alone, had an initial elongation at break of only 95% and a significant decrease in acid resistance. This may be because the HDI trimer leads to a high crosslinking density and increased brittleness, resulting in a low elongation. Comparative Example 9, which uses only liquefied MDI, shows that the tensile strength retention rate after acid treatment is only 78%, and the insufficient crosslinking density leads to the deterioration of the resistance to media. In Comparative Example 17, when HDI biuret was used instead of HDI trimer, the retention rate of tensile strength after acid treatment decreased to 82%, and the acid resistance of the biuret crosslinking network was weaker than that of the isocyanurate network.

[0071] ②Isocyanate composition balance ensures overall performance.

[0072] The isocyanate composition in Comparative Examples 12 and 13 was unbalanced. The excessive proportion of HDI trimer led to excessive crosslinking density and brittle adhesive layer. Specifically, the tensile strength retention rate of Comparative Example 12 after low temperature + acid treatment decreased to 72%, and that of Comparative Example 13 further decreased to 50%, making it impossible to balance strength and low temperature toughness.

[0073] (4) Comprehensive advantages compared with existing technologies Compared with Comparative Example 18 (polyether-type acid-resistant two-component polyurethane adhesive, CN103045153A), the acid treatment tensile strength retention rate of the example was increased from 70% to 89% or more, and the low temperature + acid treatment tensile strength retention rate was increased from 55% to 85% or more, achieving a dual breakthrough in acid resistance and low temperature resistance. Compared with Comparative Example 19 (polyester-type acid and alkali resistant reactive hot melt adhesive, CN113831885A), the tensile strength retention rate after acid treatment in this example increased from 42% to 89% or more, and the tensile strength retention rate after low temperature + acid treatment increased from 28% to 85% or more. The strong acid resistance performance is significantly superior, solving the problem of severe hydrolysis of polyester system in strong acid environment. Compared with Comparative Example 20 (PCDL type polyurethane elastomer sealing material, CN113461905A), the tensile strength retention rate of the low temperature + acid treatment in this example was increased from 40% to 85% or more, which solved the defects of high cross-linking density PCDL elastomers being brittle at low temperatures and unable to adapt to low temperature working conditions.

[0074] In summary, under the synergistic effect of multiple components such as soft segment compounding, functional modification and crosslinking network optimization, Examples 1-7 show significantly better acid resistance retention rate and low temperature retention rate than the comparative examples with missing, replaced or unbalanced proportions of any single component, and are also significantly better than the three representative schemes in the prior art, proving the rationality and significant superiority of the formulation composition of the present invention.

[0075] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. An acid-resistant polyurethane adhesive, characterized in that, It is composed of component A and component B mixed at an NCO / OH molar ratio of 1:1.12; Component A comprises, by weight: 51-82 flexible chain segments Chain extender 8-15 parts, 11-23 parts of functional filler 1-2.5 parts of coupling agent, Component B comprises, by weight: 65-85 parts of liquefied MDI 15-35 parts of HDI trimer; The flexible segment includes polycarbonate diol, hydroxyl-terminated polybutadiene, and bi-hydroxymethyl-terminated polydimethylsiloxane. The chain extender includes 2,5-furandiethanol and 1,3-adamantimethanol; The functional fillers include acid-resistant fillers and fumed silica.

2. The acid-resistant polyurethane adhesive according to claim 1, characterized in that, By weight, 40-60 parts of polycarbonate diol, 8-16 parts of hydroxyl-terminated polybutadiene, 3-6 parts of hydroxymethyl-terminated polydimethylsiloxane, 4-7 parts of 2,5-furandimethylol, and 4-8 parts of 1,3-adamantanedimethyl.

3. The acid-resistant polyurethane adhesive according to claim 1, characterized in that, The acid-resistant filler includes silica powder, mica powder, and barium sulfate.

4. The acid-resistant polyurethane adhesive according to claim 3, characterized in that, The functional filler, by weight, comprises 10-20 parts acid-resistant filler and 1-3 parts fumed silica.

5. The acid-resistant polyurethane adhesive according to claim 1, characterized in that, The coupling agent is silane coupling agent KH-550.

6. The acid-resistant polyurethane adhesive according to claim 1, characterized in that, Component A also includes 3.05 to 9.2 parts of additives.

7. The acid-resistant polyurethane adhesive according to claim 6, characterized in that, The additives include polycarbodiimide, bismuth acetylacetonate, and dioctyl terephthalate.

8. The acid-resistant polyurethane adhesive according to claim 7, characterized in that, By weight, 2-4 parts of polycarbodiimide, 0.05-0.2 parts of bismuth acetylacetonate, and 1-5 parts of dioctyl terephthalate.

9. The method for preparing the acid-resistant polyurethane adhesive according to any one of claims 1 to 8, characterized in that, Includes the following steps: (1) Preparation of component A: ① Raw material pretreatment: The flexible segments, chain extenders and dioctyl terephthalate are vacuum dehydrated, and the functional fillers are oven dried. ② Raw material mixing and dispersion: Add flexible segments, chain extenders and dioctyl terephthalate into the reaction vessel, heat and stir to disperse until a uniform and transparent mixture is formed; ③ Additives: After the mixture obtained in ② has cooled down, add coupling agent, functional filler, polycarbodiimide, and bismuth acetylacetone, continue stirring and dispersing, degas and discharge to obtain component A; (2) Preparation of component B: Liquid MDI and HDI trimer are added to a dry reaction vessel in proportion, stirred and mixed evenly under nitrogen protection, and discharged after degassing to obtain component B. (3) Two-component mixing: Mix component A and component B in proportion under nitrogen protection and stir until uniform before applying.

10. The use of the acid-resistant polyurethane adhesive according to any one of claims 1 to 8, characterized in that, The adhesive is used for bonding and sealing in low-temperature acidic corrosive environments, specifically including bonding and anti-corrosion sealing of interfaces of chemical pipelines, bonding and sealing of linings of pickling equipment, sealing and anti-corrosion repair of joints of chemical storage tanks, and sealing and bonding of acidic raw material storage and transportation containers; the adhesive can withstand low-temperature conditions down to -20°C.

Citation Information

Patent Citations

  • Acid liquor corrosion resistant dual-component polyurethane adhesive as well as preparation method and application thereof

    CN103045153A

  • Anti-acid solution corrosion dual-component polyurethane adhesive and preparation method of same

    CN109401713A

  • Polycarbonate type polyurethane elastomer sealing material as well as preparation method and application thereof

    CN113461905A

  • Polyurethane hot melt adhesive with high bonding strength and acid and alkali reaction resistance, and preparation method thereof

    CN113831885A